A refractive optical device potentially masking an intraocular tumor. Issue 4 (April 2020) - Edington, Magdalena; Connolly, Julie; Lockington, David; Cauchi, Paul; Chadha, Vikas
Abstract : A 62-year-old woman was referred with reduced vision in her left eye and suspected retinal detachment. Bilateral laser in situ keratomileusis with KAMRA corneal inlay insertion was performed in the left eye 2 years earlier. On examination, a shadow from the corneal inlay limited posterior segment examination even with dilated fundoscopy, but a temporal raised lesion extending over the macula was noted. Ocular ultrasound confirmed a large tumor consistent with malignant melanoma, requiring enucleation. It is unclear whether the patient had baseline dilated fundoscopy before corneal inlay implantation; however, a pinhole effect for the patient will cause a pinhole effect for the clinician, potentially limiting the fundal view. The authors emphasize the importance of appropriate informed consent patients, including discussion of rare risks and complications, which can have profound implications. In this case, the elective refractive procedure potentially masked an intraocular tumor. Enucleation may have been avoided if the lesion had been identified at an earlier stage.